ISO/IEC 38500 : a pocket guide - Calder, Alan, 1957- (IT Governance Publishing, 2019)
This useful pocket guide is an ideal introduction for those wanting to understand more about ISO 38500. It describes the scope, application and objectives of the Standard and outlines its six core principles.